Transformasi Media Pembelajaran Digital Dalam Mendukung Pembelajaran Hybrid Di Perguruan Tinggi - Agus Jatmiko; A'vi Amelia; Diah Irdiyana Rizqi; Αmia Kasmila; A'la Nirotul Fikri (WISE Pendidikan Indonesia, 2026)
This study aims to analyze the transformation of digital learning media in supporting the implementation of hybrid learning in higher education and its implications for learning effectiveness. The rapid development of digital technology and the increasing adoption of hybrid learning have encouraged higher education institutions to integrate digital learning media into teaching and learning processes. This study employed a qualitative approach using Systematic Literature Review (SLR), in which data were collected from scientific journal articles, books, conference proceedings, and other relevant academic publications. The collected literature was analyzed through data reduction, classification, comparison, interpretation, and synthesis to obtain a comprehensive understanding of the research topic. The findings indicate that digital learning media contribute significantly to improving learning flexibility, lecturer–student interaction, accessibility to learning resources, and students' digital competencies. Various digital platforms, including Learning Management Systems (LMS), video conferencing applications, interactive multimedia, and cloud-based learning environments, have enhanced the effectiveness of hybrid learning. However, several challenges remain, including technological infrastructure limitations, unequal digital literacy, and disparities in access to digital technologies. The study concludes that the transformation of digital learning media represents a strategic approach to developing innovative, adaptive, and sustainable hybrid learning practices in higher education.